Neuroinflammatory responses to traumatic brain injury: etiology, clinical consequences, and therapeutic opportunities - Lozano, Diego (Neuropsychiatr Dis Treat, 2015)
Traumatic brain injury (TBI) is a serious public health problem accounting for 1.4 million emergency room visits by US citizens each year. Although TBI has been traditionally considered an acute injury, chronic symptoms reminiscent of neurodegenerative disorders have now been recognized. These progressive neurodegenerative-like symptoms manifest as impaired motor and cognitive skills, as well as stress, anxiety, and mood affective behavioral alterations. TBI, characterized by external bumps or blows to the head exceeding the brain’s protective capacity, causes physical damage to the central nervous system with accompanying neurological dysfunctions. The primary impact results in direct neural cell loss predominantly exhibiting necrotic death, which is then followed by a wave of secondary injury cascades including excitotoxicity, oxidative stress, mitochondrial dysfunction, blood–brain barrier disruption, and inflammation. All these processes exacerbate the damage, worsen the clinical outcomes, and persist as an evolving pathological hallmark of what we now describe as chronic TBI. Neuroinflammation in the acute stage of TBI mobilizes immune cells, astrocytes, cytokines, and chemokines toward the site of injury to mount an antiinflammatory response against brain damage; however, in the chronic stage, excess activation of these inflammatory elements contributes to an “inflamed” brain microenvironment that principally contributes to secondary cell death in TBI. Modulating these inflammatory cells by changing their phenotype from proinflammatory to antiinflammatory would likely promote therapeutic effects on TBI. Because neuroinflammation occurs at acute and chronic stages after the primary insult in TBI, a treatment targeting neuroinflammation may have a wider therapeutic window for TBI. To this end, a better understanding of TBI etiology and clinical manifestations, especially the pathological presentation of chronic TBI with neuroinflammation as a major component, will advance our knowledge on inflammation-based disease mechanisms and treatments.